Perancangan Aplikasi Android Untuk Memonitoring Salinitas dan Suhu Air Aquarium pada Budidaya Ikan Badut - Malika Sahnah; Yenniwarti Rafsyam (Spektral, 2022)
Clown fish is a fish that is widely cultivated by farmers in aquariums. In its cultivation, there are several parameters that need to be considered, namely air salinity levels ranging from 29 PPT - 37 PPT and air temperatures ranging from 25°C-30°C. To make it easier to monitor salinity and temperature in the aquarium, the NEMOKU application was created for a monitoring system and remote control of salinity and air temperature through the Android application, which has a control system in the form of an aquarium heater, as well as fresh and salt water pumps. The NEMOKU application has an automatic and manual monitoring system. In the manual system, the fish farmer activates the system through the application, according to the conditions of the aquarium. If the salinity is <29 PPT, the farmer activates the salt water pump, if the salinity value is >37 PPT, activates the fresh water pump and if the temperature is <25°C, activates the aquarium heater. In an automatic system, the system will automatically activate to maintain the salinity and temperature in the aquarium. From the tests carried out, the system that has been designed works well in sending salinity and temperature data as well as remote control. The specifications of the tool used for applications made using Android Studio Version Bumblebee software, laptops with Intel® Core TM i3 2370 M CPU @ 2.8 GHz, 4 GB Memory, 500 GB Harddisk and 14 inches Monitor.